Advances in the Study of AI-assisted Diagnosis and Rehabilitation of ASD - Bosen MA; Xiaorong ZENG; Ran GONG; Farui LI (康复学报)
This paper reviews the research on AI-assisted diagnosis and rehabilitation of autism spectrum disorder (ASD) with the purpose of enhancing relevant studies in China. ASD is a neurodevelopmental disorder characterized by impairment in communication skills, social interactions, as well as restricted, repetitive, and stereotyped patterns of behavior. As a spectrum disorder, it demonstrates obvious between-subgroup as well as within-subgroup heterogeneity. Despite the rapid increase in the prevalence of ASD in recent years, the medical facilities and staff for its early diagnosis and rehabilitation are still in severe shortage. With the advancement of artificial intelligence (AI) technology, AI-assisted diagnosis and rehabilitation of ASD have become a research focus. The AI-assisted diagnosis research analyzes relevant data mainly by training the artificial neural network. The data include: ①brain imaging data from the ASD group and the matched group.②multimodal data of speech, movements and facial expressions produced by infants or children with ASD and data of the diagnostic process. With regard to rehabilitation training, AI-assisted non-robot intervention equipment and robot intervention equipment are widely used in research. While early research on rehabilitation with non-robot intervention equipment mainly focuses on the single skill training, recent studies have gradually shifted to the comprehensive training due to the technological advancement of human-computer interaction and virtual reality (VR). Different from the single skill training, the comprehensive training is not only concerned with communicative competence, but also creates situations close to real life. As for robot intervention equipment, while some studies explore methods and effectiveness of using robots to teach autistic children, others discuss the training of the ASD group's ability to perceive movements or combine the use of robots with traditional intervention techniques. Two advances in this line of research are as follows: ①paying more attention to people with ASD, especially autistic children's psychological characteristics and user experience.②starting to develop individualized rehabilitation training programs which are in urgent need in ASD rehabilitation training. In China, the research on AI-assisted diagnosis and rehabilitation has drawn wide attention from researchers and medical practitioners. However, the research findings and their application can barely meet the demand for high-quality diagnosis and rehabilitation training for ASD population. Drawing on the overseas research, Chinese researchers in relevant fields can expand their research in the following three aspects: encouraging collaborations among different disciplines such as computer science, speech pathology, linguistics etc.; promoting individualized intervention, and developing rehabilitation training equipment in line with the psychological characteristics and preferences of the ASD group in China.